ЧТО ЖЕ ЛУЧШЕ - КАВКАЗ ИЛИ АЛЬПЫ? - Шолпо В.Н. (My University, 2003)
Fortes and drawbacks of quantitative assessment of relief beauty of the Alps and the Caucasus made by M.P. Zhidkov and E.A. Likhacheva (Geomorphology, 2002 № 3) are considered. The author suggests using the fractal characteristics and "the law of harmony" by M. Marutaev for such evaluations.
Keywords: 551.4.035>712.01(234.3+234.9)